Mappings with finite length distortion and Riemann surfaces - Ryazanov, V.I.; Volkov, S.V. (Доповіді НАН України, 2020)
We prove a series of criteria in terms of dilatations for the continuous and homeomorphic extension of the
map pings with finite length distortion between domains on Riemann surfaces to the boundary. The criterion for
the continuous extension of the inverse mapping to the boundary is turned out to be a very simple condition on the
integrability of the dilatations in the first power. Moreover, the domain of the mapping is assumed to be locally
connected on the boundary and its range has a weakly flat boundary. The criteria for the continuous extension of
the direct map pings to the boundary have a much more refined nature. One of such criteria is the existence of a
majorant for the dilation in the class of functions with finite mean oscillation, i.e., having a finite mean deviation
from its mean value over infinitesimal disks centered at the corresponding boundary point. A stronger (but simpler)
one is that the mean value of the dilatation over infinitesimal disks centered at the corresponding boundary point is
finite. The domain is again assumed to be locally connected on the boundary and its range has a strongly accessible
boundary. We give also many other criteria for the continuous extension of the direct mappings to the boundary.
As consequences, the corresponding criteria for a homeomorphic extension of mappings with finite length distortion
to the closures of domains are obtained. У термінах дилатацій доведено ряд критеріїв для неперервного та гомеоморфного продовження на границю відображень зі скінченним спотворенням довжини між областями на ріманових поверхнях. Критерієм
для неперервного продовження обернених відображень на границю є дуже проста умова про інтегрованість дилатації в першому степені. При цьому область визначення відображення передбачається локально
зв'язною на границі, а область значень — зі слабо плоскою границею. Критерії для неперервного продовження на границю прямих відображень мають набагато тоншу природу. Один із критеріїв полягає в існуванні мажоранти дилатації в класі функцій зі скінченним середнім коливанням, тобто таких, що мають кінцеве середнє відхилення від свого середнього значення над інфінітезимальними (нескінченно малими)
колами з центром у відповідній граничній точці. Більш жорстка, але більш проста вимога полягає в тому,
що середнє значення дилатації над інфінітезимальними колами з центром у відповідній граничній точці
скінченне. Область визначення знову передбачається локально зв'язною на границі, а область значень — із
сильно досяжною границею. Також наведено багато інших критеріїв неперервного продовження на границю прямих відображень. Як наслідки отримуємо відповідні критерії для гомеоморфного продовження на границю областей відображень зі скінченним спотворенням довжини. В терминах дилатаций доказан ряд критериев для непрерывного и гомеоморфного продолжения на границу отображений с конечным искажением длины между областями на римановых поверхностях. Критерием для непрерывного продолжения обратных отображений на границу оказывается очень простое
условие об интегрируемости дилатаций в первой степени. При этом область определения отображения
предполагается локально связной на границе, а область значений — со слабо плоской границей. Критерии
для непрерывного продолжения на границу прямых отображений имеют гораздо более тонкую природу.
Один из критериев состоит в существовании мажоранты дилатации в классе функций с конечным средним колебанием, т. е. имеющих конечное среднее отклонение от своего среднего значения над инфинитезимальными (бесконечно малыми) кругами с центром в соответствующей граничной точке. Более сильное, но более простое требование состоит в том, что среднее значение дилатации над инфинитезимальными кругами с центром в соответствующей граничной точке конечно. Область определения снова
предполагается локально связной на границе, а область значений — с сильно достижимой границей. Также приведены многие другие критерии непрерывного продолжения на границу прямых отображений. В качестве следствий получаются соответствующие критерии для гомеоморфного продолжения в замыкание областей отображений с конечным искажением длины.